Factors influencing employee's intention to stay in Petronas Chemicals Group Berhad (PCGB) / Hidayu Jamil - Jamil, Hidayu (Faculty of Business and Management, 2020)
Intention to stay can be defined as the employee's willingness to remain or to stay within an organization. As the issue of employee's turnover is widely become the problem for most of organizations and industries globally, there is a need for the employer to reduce it by understanding the factors that potentially influence the intention of employees to stay. By getting to know the level of intention to remain in the company, so the employer could reduce high recruitment cost in order to replace them. Additionally, the employer could put extra efforts in retaining the employees subsequently when they knew what makes the employee leave the organization. Intention to stay among employee's tend to have correlation with the organizational commitment. This study is to determine the potential factors that may influence intention to stay among employees in PETRONAS Chemicals Group Berhad (PCGB), Kuala Lumpur. The data was retrieved from 196 questionnaires targeting all employees in the company. Statistical Package for Social Science (SPSS) is used to analyze the results and it was found that intention to stay have a significant positive relationship with effective commitment and normative commitment, but no relationship with continuance commitment. Hence, the employer is recommended to focus on how to increase the employee's continuance commitment such as giving more attention to their well-being and appreciate their hard works while they are in the company.